NECROSTATIN-1 ATTENUATES MITOCHONDRIAL DYSFUNCTION IN NEURONS AND ASTROCYTES FOLLOWING NEONATAL HYPOXIA–ISCHEMIA - CHAVEZ-VALDEZ, R. (2012)
Receptor interacting protein (RIP)-1 kinase activity mediates a novel pathway that signals for regulated necrosis, a form of cell death prominent in traumatic and ischemic brain injury. Recently, we showed that an allosteric inhibitor of RIP-1 kinase activity, necrostatin-1 (Nec-1), provides neuroprotection in the forebrain following neonatal hypoxia–ischemia (HI). Because Nec-1 also prevents early oxidative injury, we hypothesized that mechanisms involved in this neuroprotection may involve preservation of mitochondrial function and prevention of secondary energy failure. Therefore, our objective was to determine if Nec-1 treatment following neonatal HI attenuates oxidative stress and mitochondrial injury. Postnatal day (p) 7 mice exposed to HI were injected intracerebroventricularly with 0.1 μL (80 μmol) of Nec-1 or vehicle. Nec-1 treatment prevented nitric oxide (NO•), inducible nitric oxide synthase (iNOS) and 3-nitrotyrosine increase, and attenuated glutathione oxidation that was found in vehicle-treated mice at 3 h following HI. Similarly, Nec-1 following HI prevented: (i) up-regulation of hypoxia inducible factor-1 alpha (HIF-1α) and BCL2/adenovirus E1B 19 kDa protein-interacting protein 3 (BNIP3) expression, (ii) decline in mitochondrial complex-I activity, (iii) decrease in ATP levels, and (iv) mitochondrial structural pathology in astrocytes and in neurons. Up-regulation of glial fibrillary acidic protein (GFAP) following HI was also prevented by Nec-1 treatment. No differences by gender were observed. We conclude that Nec-1 immediately after HI, is strongly mitoprotective and prevents secondary energy failure by blocking early NO• accumulation, glutathione oxidation and attenuating mitochondrial dysfunction.